The Analysis of Learning Model Interaction Based On Project Based Learning Integrated WhatsApp Messenger as Mobile Learning to the Students Learning Outcomes and Critical Thinking Skills - Sulistyaning Kartikawati (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The purpose of this study was to determine the interaction of learning model based onProject Based Learning integrated WhatsApp Messenger as a mobile learning to thelearning outcomes and critical thinking skills of students. This research method usedExperimental Method with pretest-postest control group design. The sampling of procedureused cluster sampling technique consisted of VA class as experiment class as much as 17students and VB as control class which are 17 students. The data collection techniques usedobservation, documentation, interviews, questionnaires, and tests. Statistical analysis in thisstudy used t-test analysis to find the interaction of application of learning model based onProject Based Learning integrated WhatsApp Messenger as mobile learning to the learningoutcomes and students' critical thinking ability. The results showed that the value of t-testwas 8.462. The t-table means that there was an interaction of application of learning modelbased on Project Based Learning integrated WhatsApp Messenger as a mobile learningtoward learning outcomes and students' critical thinking ability. The t-table of 1.745 with asignificance level of 5% indicates that the value of t-test was greater than t-table, it meansthat there was an interaction of learning model based on Project Based Learning integratedWhatsApp Messenger as a mobile learning to the learning outcomes and critical thinkingskills of students.Keywords: Project Based Learning, WhatsApp Messenger, Mobile Learning, Learning Outcomes,Critical Thinking Skill